2022
DOI: 10.1155/2022/2271650
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of Nostalgia Emotional Experience, Rural Tourism Environment Cognition, and Consumption Willingness Based on Big Data Technology

Abstract: As the primary research vehicle, rural tourism is used in this paper to examine urban visitors’ “homesickness.” This research explores the effects of homesickness on tourists’ perceptions of travel destinations and consumption intentions through qualitative analysis, logistic empirical analysis, and questionnaire survey. This work also explores the behavioral traits of customers’ purchase intentions from the perspective of a “big data” environment, and it constructs the relevant consumption behavior model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Rural tourism enables the elderly to relive past lives [58]. The rural lifestyle can arouse tourists' nostalgia [103], and rural scenes and objects can attract nostalgic elderly [104]. The RSHTUE destination lifestyle attracts the nostalgic elderly, whose arrival raises the RSHTUE demand.…”
Section: Cultural Drivers Of Demandmentioning
confidence: 99%
“…Rural tourism enables the elderly to relive past lives [58]. The rural lifestyle can arouse tourists' nostalgia [103], and rural scenes and objects can attract nostalgic elderly [104]. The RSHTUE destination lifestyle attracts the nostalgic elderly, whose arrival raises the RSHTUE demand.…”
Section: Cultural Drivers Of Demandmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%